The spectrum of HIV-1 related cancers in South Africa. - Sitas, F; Pacella-Norman, R; Carrara, H; Patel, M; Ruff, P; Sur, R; Jentsch, U; Hale, M; Rowji, P; Saffer, D; Connor, M; Bull, D; et al. (2000)
Despite the high prevalence of infection by the Human Immunodeficiency Virus (HIV) in South Africa, information on its association with cancer is sparse. Our study was carried out to examine the relationship between HIV and a number of cancer types or sites that are common in South Africa. A total of 4,883 subjects, presenting with a cancer or cardiovascular disease at the 3 tertiary referral hospitals in Johannesburg, were interviewed and had blood tested for HIV. Odds ratios associated with HIV infection were calculated by using unconditional logistic regression models for 16 major cancer types where data was available for 50 or more patients. In the comparison group, the prevalence of HIV infection was 8.3% in males and 9.1% in females. Significant excess risks associated with HIV infection were found for Kaposi's sarcoma (OR=21.9, 95% CI=12.5-38.6), non-Hodgkin lymphoma (OR=5.0, 95%CI=2.7-9.5), vulval cancer (OR=4.8, 95%CI= 1.9-12.2) and cervical cancer (OR= 1.6, 95%CI= 1.1-2.3) but not for any of the other major cancer types examined, including Hodgkin disease, multiple myeloma and lung cancer. In Johannesburg, South Africa, HIV infection was associated with significantly increased risks of Kaposi's sarcoma, non-Hodgkin lymphoma and cancers of the cervix and the vulva. The relative risks for Kaposi's sarcoma and non-Hodgkin lymphoma associated with HIV infection were substantially lower than those found in the West.